Bandido: the life and times of Tiburcio Vasquez (University of Oklahoma Press, 2010)
Description Not Provided
Sons of the conquistadores , In old Monterey , A boyhood among bandits , The Roach-Belcher feud , He never showed the white feather , The big break , Bandido , In the saddle with Juan Soto , Stagecoach robber , Shootouts and lynchings , Ride the high country , "I'm a ranger, by God!" , The Tres Pinos tragedy , Pursuit and betrayal , Raiders of the San Joaquin , Harry Morse tries his hand , Manhunt in Los Angeles , Dead or alive , The murder trial , To die game , Epilogue: buried treasure, social banditry, and other myths.

Badge and buckshot: lawlessness in old California (University of Oklahoma Press, 1987)
Description Not Provided

Gentleman bandit: the true story of Black Bart, the Old West's most infamous stagecoach robber (Hanover Square Press, 2023)
"Black Bart is widely regarded today as not only the most notorious stage robber of the Old West but also the best behaved. Over his lifetime, Black Bart held up at least twenty-nine stagecoaches in California and Oregon with mild, polite commands, stealing from Wells Fargo and the US mail but never robbing a passenger. Such behavior earned him the title of a true 'gentleman bandit.' His real name was Charles E. Boles, and in the public eye, Charles lived quietly as a boulevardier in San Francisco, the wealthiest and most exciting city in the American West. Boles was an educated man who traveled among respectable crowds. Because he did not drink, fight or consort with prostitutes, his true calling as America's greatest stage robber was never suspected until his final capture in 1883. Sheriffs searched and struggled for years to find him, and newspaper editors had a field day reporting his exploits. Legends and rumors trailed his name until his mysterious death, and his ultimate fate remains one of the greatest mysteries of the Old West. Now historian John Boessenecker sheds new light on Black Bart's beginnings, reputation and exploits, bringing to life the glittering story of the mysterious stage robber who doubled as a rich, genteel socialite in the golden era of the Wild West"--
You fine-haired sons of bitches , The gold hunter , The rifleman , The charge of the light brigade , Wounds of war , I have had a rough life of it , The poet highwayman , Wells Fargo detective , The gentleman bandit , The chances I have to take , Buckshot for Black Bart , Throw down the box , Fiasco at Funk Hill , Black Bart throws up the sponge , That telltale handkerchief , A war of words , San Quentin sojourn , I have abandoned crime of every kind , Black Bart rides again , Myth and mystery.

Gold dust and gunsmoke: tales of gold rush outlaws, gunfighters, lawmen, and vigilantes (John Wiley, 1999)
TALES OF GOLD RUSH OUTLAWS, GUNFIGHTERS, LAWMEN, AND VIGILANTES.
"Boys, I believe I've found a gold mine" , First blood , Judge Lynch , Gringos and greasers , Bring me the head of Joaquin Murrieta , Pillagers or patriots? , The whores in "51 , Bears, bulls, and are knuckles , I'll die before I'll run , The field of honor , Pirates of the placers , Gold rush lawmen , Enforcing the law , Gold rush gunfighters.